IDENTIFIKASI LAMA PERSALINAN DI PMB NGUDI SARAS, JATEN, KARANGANYAR TAHUN 2021 - Suwarnisih Suwarnisih (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2023)
ABSTRACT. Childbirth is a series of processes that end with the expenditure of products of conception (Varney, 2008). Each birth is unique in that some deliveries are very short and some take so long that it leaves a mother hopeless, while some are problematic for both the mother and the baby (Simkin, 2007). Factors that affect the closeness of labor include maternal factors, fetal factors, and birth canal factors. Maternal factors include age, age, and parity. The fetal factors include attitude, location, malposition and malpresentation, large fetus, and congenital abnormalities such as hydrocephalus. Factors of the birth canal include a narrow pelvis, tumors in the pelvis, abnormalities in the cervix and vagina (Prawirohardjo, 2006). The aim of this study was to determine the length of labor at PMB Ngudi Saras Jaten, Karanganyar. Descriptive observational research method. The population in this study were 72 people. The sampling technique used was